Plant in vitro cultures: A promising and emerging technology for the feasible production of antidiabetic metabolites in Caralluma tuberculata - Ali, Amir; Mashwani, Zia-ur-Rehman; Ahmad, Ilyas; Raja, Naveed Iqbal; Mohammad, Sher; Khan, Safir Ullah (Frontiers in Endocrinology, 2022)
Caralluma tuberculata, a medicinal and edible plant of the genus Caralluma, belongs to the family Asclepiadaceae. Traditionally, its succulent stems are used as folk medicine against life-threatening Diabetes mellitus disease. Their antidiabetic potential is due to the presence of various secondary metabolites (pregnane glycosides, flavone glycosides, megastigmane glycosides, polyphenols, ferulic acid, quercetin, bitter principles, etc.,) which act as effective and safe antidiabetic agents. The mechanism of these bioactive secondary metabolites in C.tuberculata herbal medicine is: to lower blood glucose level, stimulate beta cells of the pancreas to release more insulin, enhances the sensitivity of insulin receptor, inhibit the action of glucagon, inhibit hydrolysis of glycogen, and increase the use of glucose in tissues and organ. However, over-exploitation, alteration in natural environmental conditions, less seed viability, and slow growth rate are responsible for the extinction of species from natural habitats and then becoming critically endangered species of the International Union for Conservation of Nature red list categories. Therefore, limited availability is not fulfilling the higher market demands worldwide to use the C. tuberculata plant as an antidiabetic drug. Thus, for conservation and sustainable utilization, researchers are working across the globe to conserve and improve biomass along with their secondary metabolites profile through the intervention of in vitro approaches on C. tuberculata. The current review described the recent progress of antidiabetic phytoconstituents, their cellular mechanism, and their subsequent clinical outcomes in drug discovery management of DM. Moreover, in vitro methods such as callus cultures, micropropagation, and nanoelicitation strategies for conserving and producing bioactive secondary metabolites have been concisely reviewed and discussed.